AN EMPIRICAL ANALYSIS OF CORPORATE CAPITAL STRUCTURE AND FINANCIAL PERFORMANCE OF LISTED CONGLOMERATES IN NIGERIA - Lukman Adebayo Oke; Daud Omotosho Saheed; Yusuf Olamilekan Quadri (Copernican Journal of Finance & Accounting, 2019)
The relationship between capital structure and firms’ financial performance has attracted the attention of many researchers both locally and globally. The paucity of empirical evidence from Nigeria in this regard, especially on Nigerian conglomerate firms, portends the need for further research. Against this backdrop, the study investigated the impact of capital structure on the financial performance of listed conglomerates in Nigerian using descriptive statistics, pairwise correlation and panel data regression technique to analyze the secondary data extracted from the annual reports and accounts of the six (6) selected conglomerates for the period 2008 to 2017. The study found that financial leverage proxy by total debt ratio, long-term debt ratio and short-term debt ratio have significant impact on the selected firms’ financial performance proxy by return on assets, except debt to equity ratio that reveals an insignificant impact on return assets (ROA). Firm size and growth also reported a significant effect on the financial performance of the selected firms. The findings is in tandem with the proposition of the agency cost theory in the Nigeria settings but with caution considering the facts that firms in Nigeria were largely finance through short term debt obligation as against long term debt funding that was presumed in the agency cost theoretical proposition. It is therefore recommended that managers of companies should be guided when seeking credit advances from the financial market as it is important when considering the appropriate capital mix that optimize firm value.